THE ROLE OF EMOTIONAL INTELLIGENCE IN ENHANCING JOB PERFORMANCE AND WELL-BEING: INSIGHTS FROM ZOOLOGICAL RESEARCH AND APPLICATIONS IN IT PROFESSIONALS (CAHIERS MAGELLANES-NS, 2024)
Emotions are significant behavioral reactions that influence one's own achievement as well as other facets of life. Emotional intelligence (EI) is the capacity to "observe and express emotion accurately, to understand the emotion and emotional knowledge, to use emotions to facilitate thought and to regulate emotions." People with high emotional intelligence may be better able to comprehend their ideas and feelings and reach their full potential. Therefore, EI is undoubtedly a vital component of a person's personality. The ability to identify and manage our own emotions, as well as those of others, has been referred to as emotional intelligence. Employee performance is defined as the degree to which a worker fulfills his or her obligations, functions, and responsibilities within a company.Organizations are aware of how negatively productivity and profit are impacted by subpar work performance. Organizational outcomes are significantly influenced by psychological concepts like emotional intelligence (EI). Academic studies have also demonstrated a connection between EI and workers' well-being, their ability to handle stress, low employee turnover, and burnout. Organizations are very concerned about job performance because the demanding nature of the IT business forces employees to prioritize their physical and mental well-being. Furthermore, parallels can be drawn between emotional intelligence observed in animal behavior and its application in enhancing human performance and well-being. This research, using mixed methods, examines how Emotional Intelligence (EI) affects IT professionals' job performance and well-being, integrating insights from zoological research. A demographic profile-containing questionnaire was used to conduct the survey. Data analysis techniques from descriptive statistics, correlation, and regression were used to evaluate quantitative data. The results of this study demonstrate the significant impact of an employee's emotional intelligence on their well-being and productivity, offering new perspectives by incorporating zoological insights into the discussion.